Combustion and Emission Characteristics of a Spark Ignition Engine Fuelled with Biogas from Two-Phase Anaerobic Digestion (T-PAD). (May 2017) - Zhang, Yang; Zhu, Mingming; Zhang, Zhezi; Zhang, Dongke
Abstract: The performance of a small-scale spark ignition gas engine fuelled with model biogases from two-phase anaerobic digestion (T-PAD) was experimentally studied. Combustion characteristics, in terms of engine power output and thermal efficiency, and engine exhaust emissions of unburned hydrocarbon, CO and NOx were measured. The biogases from T-PAD, rich in hydrogen, were modelled with mixtures ofCH4 /H2 /CO2 with a varyingCO2 volumetric fraction from 25% – 30% and H2 /CH4 volumetric ratio from 0 to 3/7. Increasing CO2 volumetric fraction in the biogas decreased the engine power output, while increasing H2 /CH4 ratio increased the engine power output especially at high excess air ratios (the ratio of the actual air to the stoichiometric air > 1.4). For a given CO2 volumetric fraction, increasing H2 /CH4 ratio in the biogas from 0 to 3/7 significantly increased the thermal efficiency, reduced the unburned hydrocarbon and CO emissions and slightly increased NOx emission under the conditions with the excess air ratios greater than 1.4. When the engine was operating under its best condition (excess air ratio from 1.2 to 1.4), increasing H2 /CH4 ratio did not remarkably change the engine power output, thermal efficiency, the unburned hydrocarbon and CO emissions, but significantly increased the NOx emission. This study proved the feasibility of using the hydrogen-rich T-PAD biogas as a renewable fuel for power generation in small-scale spark ignition engines.